Síntese, caracterização e estudo das propriedades fotofísicas de SiO2-GeO2 VAD encapsulada com Eu2O3 - Oliveira, Larissa Helena de (Universidade Federal de São Carlos, 2008)
Some materials can be encapsulated with metals, inorganic solids and biomolecules, in a nanometric scale, to form a nanocomposite which has specific properties that can be open to research and technology works. In the literature, they are represented as core@shell. When silica particles are coated with a luminescent material, as the Eu2O3, the final material will have different properties from the core and the shell material. The silica used as a core in this work is the silica-germania VAD, synthesized by the Vapor-phase Axial Deposition (VAD) technique, which has been given by the PhD. Carlos K. Suzuki from FEM-UNICAMP. The luminescent properties of the Eu3+ ion in the SiO2-GeO2@Eu2O3 material, has been studied to get some information about the environment around this ion during the heat treatment process. The emission spectra of the samples presented the main Eu3+ characteristics 5D0→7FJ ( J= 0,1,2,3, 4) bands. The degradation of the polymeric shell which involves the Eu3+ ions degradation occurs as the temperature increases, causing structural changes around this ion. With its degradation, the Eu3+ ion is incorporated to the silica-germania matrix. The interaction between this ion and the matrix is through Ge-O-Eu linkages, which suppress the Eu3+ luminescence. The same luminescence behavior is observed for the SiO2@Eu2O3 and SiO2@Eu2O3 spherical samples heat treat in the same temperatures. The lifetime curves for these materials when they are excited in its respective maximum of emission and excitation, present a mono-exponential feature and the values are higher than Eu2O3 pure. This material presented some novel optical properties, which makes it in a potential candidate to be used in a photonic area.
SiO2-GeO2 Soot Perform as a core for Eu2O3 nanocoating: Synthesis and Photophysical study
Keywords: Luminescência; Európio; Encapsulamento; Partículas core-shell; SiO2-GeO2; CIENCIAS EXATAS E DA TERRA::QUIMICA